International directory of company histories. Volume 176. - Johnson, Drew D.; Gale Group (Farmington Hills, Mich. St. James Press, a part of Gale, Cengage Learning, 2016)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.
180s, Inc. -- A&E Television Networks, LLC -- ActiveHealth Management, Inc. -- AdBoom Group, Inc. -- Air Algerie S.P.A. -- All-China Federation of Trde Unions -- Alton Steel Inc. -- Answers Corporation -- Anthony International -- AppLovin Corporation -- Arion Banki hf. -- Axel Springer SE -- Bai Brands, LC -- Bank for International Settlements -- BATS Global Markets, Inc. -- Beer Nuts, Inc. -- Bettys & Taylors Group Limited -- Bosque Systems, LLC -- Carvana, LLC -- Centerplate, Inc. -- CN Bio Innovations Limited -- CollegeHumor Media, Inc. -- Compania Cervecerias Unidas S.A. -- Comuto SA (BlaBlaCar) -- Davaco, Inc. -- DeVito/Verdi, Inc. -- The Doctors Company -- DraftKings, Inc. -- Ducks Unlimited, Inc. -- Ducks Unlimited, Inc. -- Egon Zehnder International AG -- ekoVenture, Inc. (Zozi) -- Evercore Partners Inc. -- Fastweb S.p.A. -- Faultless Starch/Bon Ami Company -- Fitness anywhere, LLC -- FLIR Systems, Inc. -- Funny Or Die, Inc. -- Geosansar Advisors Pvt. Ltd. -- Grede Holdings, LLC -- Griffon Corporation -- The Handel Group LLC -- Hathaway Dinwiddie Construction Company -- Hawkins, Inc. -- Hexaware Technologies Limited -- Hurco Companies, Inc. -- iCracked Inc. -- Ilim Timber -- Interactive Innovation Group, Inc. -- Intercontinental Exchange, Inc. -- Intermatic Incorporated -- Intuitive Surgical, Inc. -- Islandsbanki hf. -- James Avery Craftsman, Inc. -- James Coney Island, Inc. -- Jump Trading, LLC -- NAC Kazatomprom JSC -- King Arthur Flour Company, Inc. -- Krave Pure Foods, Inc. -- Lockton Companies Inc. -- Lockton Companies Inc. -- Lufthansa Technik Shannon Limited -- Majesco Entertainment Company -- Maker Studios, Inc. -- Manulife Financial Corporation -- Michael Best & Friedrich LLP -- MRC Global Inc. -- Naumes, Inc. -- Nesta -- New America Foundation -- Newmarket Foundation -- Newmarket Gold Inc. -- Nitro Circus Media Holdings, Inc. -- Norwich City Football Club PLC -- OCP SA -- Onion, Inc. -- Oregon Chai, Inc. -- Outbrain, Inc. -- Paramount Resources Ltd. -- Pick n Pay Stores Limited -- Ping An Insurance (Group) Company of China, Ltd. -- Raiffeisen Zentralbank Osterreich AG -- Raymond Limited -- Rdio, Inc. -- Renishaw plc -- Rotork plc -- Shimano Inc. -- Shopify, Inc. -- Southampton Football Club Limited -- Suja Life, LLC -- Tchibo GmbH -- Thorley Industries LLC -- The Trde Desk, Inc. -- Tradebot Systems, Inc. -- United States Lime & Minerals, Inc. -- W. Atlee Burpee & Co. -- Wacoal Holdings Corp. -- World Bank Group -- Wyoming Machinery Company -- XO Group Inc. -- Xoom Corporation -- Yeti Coolers, LLC -- Zara Espana S.A.
Includes bibliographical references and indexes.
Keywords: Big business -- History -- Directories; Business enterprises -- History -- Directories; Corporations -- History -- Directories